UJI KONSENTRASI PUPUK ORGANIK CAIR DAN PUPUK DAUN TERHADAP PERTUMBUHAN ANGGREK (Dendrobium sp): Pupuk organik cair , pupuk daunm anggrek dendrobium - Nurul Latif, Ika; Siswadi, Siswadi; Ratna Nurhayati, Dewi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2024)
This research, entitled Concentration Test of Liquid Organic Fertilizer and Leaf Fertilizer on the Growth of Orchids (Dendrobium sp), research on Dendrobium orchids with the Den Betty Rose Purple orchid plant, was carried out at the Bandungan Raja Bunga Orchid Garden, Semarang Regency, Central Java, from November 2023 to January 2024. This research aims is test the effect at concentration of liquid organic fertilizer and foliar fertilizer of the growth of Dendrobium orchid plants. The experimental design used was a factorial completely randomized design (CRD) with 3 treatments with 3 replications. The liquid organic fertilizer used is RBA brand fertilizer, and the foliar fertilizer used is Gaviota brand fertilizer. The observational data was analyzed using analysis of variance (ANOVA) and the results were interpreted using the honest significant difference test (BNJ) at a significance level of 5%. The parameters observed were plant height, number of leaves, leaf width and number of roots. The research results showed that the combination of using liquid organic fertilizer with the concentration of 10 ml/liter and foliar fertilizer with a concentration of 2 gr/liter had an effect on the growth of plant height, number of leaves, leaf width and number of roots.